Succinylation modification-mediated upregulation of Sp1 promotes hepatocellular carcinoma cell proliferation - Yehong Han; Xueqin Deng; Haixia Chen; Jie Chen; Wei Xu; Lanqin Liu (Discover Oncology)
Abstract Hepatocellular carcinoma (HCC) remains one of the most prevalent malignant tumors globally, characterized by high incidence and mortality rates. Despite ongoing research, the underlying molecular mechanisms of HCC development are not yet fully understood. Utilizing bioinformatic analysis, real-time quantitative reverse transcription polymerase chain reaction (RT-qPCR), and Western blot assays, we identified that the expression of specificity protein 1 (Sp1) was significantly elevated in HCC cells compared to normal cells. Knockdown of the Sp1 gene led to a marked reduction in the viability and clonogenic potential of HCC cells. Further investigation revealed that the succinylation level of Sp1 was also increased in HCC cells. The upregulation of Sp1 expression was attributed to its succinylation, mediated by KAT2A, with lysine (K)562 identified as the succinylation site. Additionally, KAT2A and Sp1 were found to influence the upregulation of mTOR phosphorylation. Collectively, these findings suggest that KAT2A-promoted succinylation of Sp1 enhances the proliferative capacity of HCC cells by activating the mTOR pathway, providing a theoretical foundation for potential therapeutic strategies against HCC.